ATRA attenuate proteinuria via downregulation of TRPC6 in glomerulosclerosis rats induced by adriamycin. (15th October 2018) - Zhang, Lei; Chen, Xiu-Ping; Qin, He; Jiang, Ling; Qin, Yuan-Han
Abstract: Objective: In this research, we explored the molecular mechanism of proteinuria in glomerulosclerosis rats and the protective effects of ATRA. Methods: This research set up three groups: SHO group, GS group, and ATRA group (15 mg/(kg d), Sigma, St. Louis, MO). The serum creatinine (Scr), urea nitrogen (BUN), and 24-h proteinuria were detected 12 weeks after administration of ATRA. The pathological and ultrastructure changes were observed under light microscope and transmission electron microscope. The protein expression of TGF-β1 and Col-IV in glomerulus was detected by immunohitochemistry method. The mRNA and the protein expression of glomerular TRPC6 were detected by RT-PCR and Western blot. Results: In the rat model of GS, the expressions of TRPC6 were significantly elevated compared with the normal rat group; however, the use of ATRA down-regulated the expression of TRPC6 in the glomeruli and attenuated glomerulosclerosis and proteinuria. Scr and BUN were also improved by the treatment of ATRA. Conclusions: Our results demonstrated that ATRA could ameliorate glomerulosclerosis and proteinuria in GS, which may be related to suppressed expression of TRPC6.